Time to shift the shift: performance effects of within-day cumulative service encounters in retail stores - Chen, Chien-Ming (2023)
This paper investigates the impact of cumulative service encounters (CSE) on sales staff's performance in retailing services. To assess the overall impact of CSE on store performance, we present an integrative framework that jointly considers two key performance indicators of retail stores (conversions and sales). We hypothesize that staff performance is negatively affected by within-day CSE, lowering both conversions and sales. Using a long panel dataset from 191 apparel stores over six calendar years (with more than 2 million store-hour observations), we empirically test the proposed framework at the granular hourly level. We find that within-day CSE have a negative and significant effect on how sales staff influences conversions and sales. We estimate that CSE are associated with an average of $9,991 revenue loss per day for the retail chain in our sample. To further illustrate how the empirical results can inform staff scheduling decisions, we present an optimization model of within-day workforce allocation. The model shows that a store could improve its sales by 2% when the store optimizes its staff schedule to offset the effect of CSE, without the requirement for increasing the staffing level. To our knowledge, this is the first study that empirically examines the negative effect of CSE on retail sales staff's productivity. Our findings contribute to both retail operations practices and the literature on workload-dependent service systems.